Super-twisting sliding mode control of grid-side inverters for wind power generation systems with parameter perturbation - Weiqi Zhang; Yanmin Wang; Muhammad Zeeshan; Fengling Han; Kai Song (International Journal of Electrical Power & Energy Systems)
Wind power generation systems (WPGSs) utilizing permanent magnet synchronous generators (PMSGs) are increasingly mandated to deliver more consistent, secure, and efficient electrical power to the grid under unpredictable weather circumstances. Effectively engineered WPGSs employ a three-phase grid side inverter (GSI) with an LCL filter linked to the grid to minimize power loss. The current control methods for WPGSs utilizing the GSI predominantly employ proportional-integral (PI) controllers, which are susceptible to fluctuations in internal and external system parameters and challenging to optimize for appropriate control gains, hence constraining the output performance of WPGSs. Thus, this paper proposes a robust control strategy for WPGSs with GSIs connected between variable speed PMSGs and grid side based on higher-order sliding mode control (HOSMC) theory. First, the GSI model is constructed by integrating the DC voltage outer loop, AC current outer loop, and AC voltage inner loop, accounting for instantaneous power fluctuations at the DC connection and perturbations in internal component parameters. Subsequently, three novel integral-type super-twisting sliding mode controllers (STSMCs) are proposed to control the time-varying active and reactive powers better exchanged between the GSI and the grid. The switching terms in traditional sliding mode control (SMC) controllers are softened to attenuate chattering. Further, the predictable control gain and time-varying control gain in three STSMC controllers are designed to minimize control system energy expenditure caused by over-regulation and prevent excessive computation of uncertainty boundaries following system disturbances. Finally, the phase trajectory convergence characteristics of each controller are analyzed, and the multi-condition simulation and experiment considering parameter perturbation are designed to validate the proposed method. The results indicate that the proposed method markedly enhances the active/reactive power response and stability of three-phase voltage/current signals under parameter perturbations, attaining a rapid consensus convergence response time of 1.5 ms for power deviations below 4.92 %, with output voltage and current harmonic content reduced by 0.27 % and 5.62 %, respectively, compared to PI control.